Research and development in intelligent systems XXXII : incorporating applications and innovations in intelligent systems XXIII, Proceedings of Al-2015, the thirty-fifth SGAI International Conference on Innovative Techniques and Applicaitons of Artificial Intelligence /: incorporating applications and innovations in intelligent systems XXIII, Proceedings of Al-2015, the thirty-fifth SGAI International Conference on Innovative Techniques and Applicaitons of Artificial Intelligence. (2015) - Unknown
No abstract available